Literature Review: Critical Analysis of Foot and Mouth Disease Control and Prevention Strategies in the Livestock Sector - Hidayah, Nurulia; Yolanda, Devia; Ramadhani, Tsaqifa Zirlyfera; Silmi, Naili (JURNAL ILMIAH PETERNAKAN TERPADU, 2025)
Foot and Mouth Disease (PMK) is one of the diseases that is easily transmitted to cloven-hoofed animals, such as cattle, goats, sheep, buffaloes, and pigs. FMD is caused by the Foot and Mouth Diseases Virus (FMDV) from the genus Aphthovirus and the family Picornaviridae. Foot and Mouth Disease has a low mortality rate and high morbidity rate and is easily transmitted. Thus causing significant material and non-material losses in the livestock sector. This study aims to analyze the risk factors for FMD outbreaks in ruminants and provide insight into the prevention and control of FMD outbreaks. This study was conducted using a literature review method of various related studies published within a period of 2 weeks. The results of the analysis show that in efforts to control FMD, an integrated approach is needed, including vaccination, biosecurity, and livestock health management. Therefore, education is needed for the community regarding early detection of FMD symptoms and how to treat it is very important to reduce losses. Collaboration between veterinary authorities, livestock breeders, and the community is expected to reduce the spread of this disease and mitigate its economic impact.